Development of a Reference Method and Materials for Quantitative Measurement of UV-Induced DNA Damage in Mammalian Cells: Comparison of Comet Assay and Cell Viability. (17th September 2022) - Atha, Donald H.; Tona, Alessandro; Reipa, Vytas
Abstract : Application of DNA damage diagnostic tests is rapidly growing, in particular for ovarian, prostate, and skin cancers; environmental monitoring; chronic and degenerative diseases; and male infertility. Such tests suffer from significant variability among different laboratories due the lack of standardization, experimental validation, and differences in data interpretation. Reference methods and materials for quantitative measurement of UVA-induced DNA damage in mammalian cells are frequently needed. In this study, we examined the use of the single-cell gel electrophoresis (comet) assay to assess the UVA-induced DNA damage in surface-attached Chinese hamster ovary (CHO) cells treated with a photosensitizer as a candidate cellular oxidative damage reference material. We found that the comet images became diffused and the viability of the cells decreased substantially (>20%) as the UVA dose and benzo [a] pyrene (BaP) concentration exceeded 6.3 J/cm 2 and 10 −6  mol/L BaP. Maintaining the conditions of exposure within this range can improve DNA damage measurement fidelity, particularly if used as a quantitative reference method and to produce materials considered as an in vitro standard for the comet assay.